Maqashid Al-Sharia in The Dynamics of Contemporary Zakat Fiqh in The North Sumatra Region - Ali Akbar; Nisful Khoiri; Asmuni Asmuni (International Journal Ihya' 'Ulum al-Din, 2023)
Zakat is an exciting and popular study today because it is not only an area of worship but also an area of muamalat (Islamic economics) that continues to grow and develop. The aim of this research is (1) to describe the development of Contemporary Zakat Fiqh in North Sumatra and (2) to describe the position of Maqasid al-Syariah as a methodology for zakat jurisprudence in North Sumatra. This type of research combines field research and library research using field and library data as the primary source. What makes this research different from others is that the research location is in North Sumatra Province, the largest city which promises the development of diverse economic sectors, diverse professions, rich sources of wealth that will produce considerable potential for zakat funds, as well as a modern management sector, provide space for the development of zakat so that it can increase the potential for zakat collection to the maximum This research is a qualitative method with collaboration between field research and literature. The theoretical basis used in this research is in contact with zakat jurisprudence in Indonesia, such as the rules for making things easier and eliminating difficulties (al-Tasyr wa raf al-haraj), the rules for changing fatwas due to changes in times (taqhyir alfatwa bi tahaqyyur) when times put needs in an emergency position. This study showed that the development of the potential of the contemporary zakat sector is entirely consistent with this theory and requires the potential of the modern zakat sector above to be a concern to formulate its law through the ijtihad development methodology, namely maqashid al-sharia to strengthen the formulation of contemporary zakat fiqh. Maqashid al-sharia on contemporary zakat fiqh in North Sumatra can be found through the values of benefit to muzakki, zakat institutions (BAZNAS), and zakat recipients/mustahik. Applying maqashid al-sharia-based contemporary zakat fiqh in North Sumatra has not been maximally practical.